Design, Synthesis, Molecular Docking, and Cholinesterase Inhibitory Potential of Phthalimide‐Dithiocarbamate Hybrids as New Agents for Treatment of Alzheimer's Disease. Issue 11 (7th October 2019) - Asadi, Mehdi; Ebrahimi, Mostafa; Mohammadi‐Khanaposhtani, Maryam; Azizian, Homa; Sepehri, Saghi; Nadri, Hamid; Biglar, Mahmood; Amanlou, Massoud; Larijani, Bagher; Mirzazadeh, Roghieh; Edraki, Najmeh; Mahdavi, Mohammad
Abstract: A novel series of phthalimide‐dithiocarbamate hybrids was synthesized and evaluated for in vitro inhibitory potentials against acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE). The anti‐cholinesterase results indicated that among the synthesized compounds, the compounds 7g and 7h showed the most potent anti‐AChE and anti‐BuChE activities, respectively. Molecular docking and dynamic studies of the compounds 7g and 7h, respectively, in the active site of AChE and BuChE revealed that these compounds as well interacted with studied cholinesterases. These compounds also possessed drug‐like properties and were able to cross the BBB. Abstract :